Young children's emotional stress reactions during the COVID-19 outbreak and their associations with parental emotion regulation and parental playfulness. Issue 6 (26th April 2022) - Shorer, Maayan; Leibovich, Liat
ABSTRACT: Children's emotional adjustment during stressogenic events is highly dependent on their parents' emotional state. The present study explored young children's emotional adjustment during the COVID19 outbreak as it relates to their exposure to stress, and their parents' emotion regulation and playfulness. A sample of 351 Israeli parents of children aged 2–7 years completed online questionnaires. The most frequent stress symptoms in children were nervousness, agitation, and aggression, separation fears and clinging. Parental difficulties in emotion regulation, and the level of exposure to stressogenic situations were both significantly associated with children's stress reactions. Parental emotion regulation fully mediated the relationship between exposure to stress and children's stress reactions. Parental playfulness was only inversely related to children's stress reaction in fathers. These findings underscore the importance of parental emotion skills for children's emotional adjustment during stressful times.